The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1177/0049475518811513
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric visceral leishmaniasis: a retrospective study on clinical manifestations, demographic features and laboratory findings of hospitalised cases in Iran between 2006 and 2016

Abstract: Visceral leishmaniasis (VL) is a neglected disease. Our retrospective study describes 38 clinical and epidemiological characteristics of VL in patients admitted to a paediatric hospital in Tehran, Iran, who came from different geographical regions, indicating that the disease has spread to most parts of the country. Some 76.3% of the children documented suffered with symptoms of the disease for two months before admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
0
8
1
Order By: Relevance
“…Another study in a pediatric hospital in Tehran mean hemoglobin concentration, mean platelet count and mean WBC count were 9.2 ± 2 g/dL, 152 ± 7.7/mL and 4.84 ± 1.6/mL, respectively. However, in comparison with our results (Hb: 8/8 ± 1.92g/dl, platelet: 185.769 ± 145.658/mL, WBC: 6.939± 4.69/mL), the mean plt and WBC count was higher in our findings ( 35 ). According to Tofighi et al laboratory results, anemia (97.1%), thrombocytopenia (91.2%), and leukopenia (67.6%) were the most common laboratory hematological abnormalities in VL.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Another study in a pediatric hospital in Tehran mean hemoglobin concentration, mean platelet count and mean WBC count were 9.2 ± 2 g/dL, 152 ± 7.7/mL and 4.84 ± 1.6/mL, respectively. However, in comparison with our results (Hb: 8/8 ± 1.92g/dl, platelet: 185.769 ± 145.658/mL, WBC: 6.939± 4.69/mL), the mean plt and WBC count was higher in our findings ( 35 ). According to Tofighi et al laboratory results, anemia (97.1%), thrombocytopenia (91.2%), and leukopenia (67.6%) were the most common laboratory hematological abnormalities in VL.…”
Section: Discussioncontrasting
confidence: 80%
“…The average hospitalization time in the treatment with L-AmB was less than other drugs with better efficacy and fewer side effects (15.3 days) in our study. Glucantime and DAmB were used in the treatment of VL in another pediatric hospital in Tehran, D-AmB for 15 days and glucantime for 4 weeks ( 35 ). In Sakari study, a 28-day course of glucantime has been used in most cases ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mean age of patients with kala-azar hospitalized in Emam Reza Hospital in Mashhad, who were reviewed by Shamsian et al, was 3.7±4 years ( 11 ). Nourian et al reported that only 7.9% of hospitalized patients with visceral leishmaniasis in Mofid Hospital in Tehran were over 10 years old ( 12 ). In addition, studies from other countries showed similar results ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Typical VL includes intermittent or continuous fever, non-tender hepatosplenomegaly, pancytopenia, leading to anemia, hemorrhages and concurrent infections ( de Araujo et al., 2012 ). However, the atypical form may be misdiagnosed with other opportunistic infections or is diagnosed with substantial delay, so early recognition and treatment are necessary ( Nourian et al., 2019 ). In this case, the patient manifested unusual clinical presentations (fatigue, splenomegaly, anemia, no fever, hemorrhages, or concurrent infections), which frequently occur in individuals with low CD4+ T-cell counts (23.01%) ( Bimal et al., 2008 ; Garg et al., 2009 ; Santos-Oliveira et al., 2010 ).…”
Section: Discussionmentioning
confidence: 99%